Preventing Adolescent Drug Abuse : Intervention Strategies. NIDA Research Monograph 47. A RAUS Review Report - National Inst. on Drug Abuse (DHHS/PHS), Rockville, MD.; Glynn, Thomas J.; National Inst. on Drug Abuse (DHHS/PHS), Rockville, MD. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1983)
This collection of papers begins with a presentation on the role of mass media campaigns in drug abuse prevention, emphasizing the need for skill development and family involvement. The next presentation addresses general and specific influences on health behavior including society, the family, peers, the school, and the individual. A three-dimensional model for health promotion is described. Community prevention projects in heart disease are presented with implications for drug abuse prevention. Research on the interplay of social, personality, and developmental factors is reviewed. The effects of alternative programming as a prevention strategy are given. School/parent group programs and research on their effectiveness are discussed. The values of drug abusers, from the perspective of belief system theory are addressed. Social skills training and educational needs are discussed. The monograph concludes with a summary of the discussions and recommendations of the participants for future research efforts. (BL)
ERIC Note: Based upon papers and discussion from the RAUS Review Conference, Rockville, MD, April 14-15, 1983.
Educational level discussed: Secondary Education.
Microfiche.
Keywords: Adolescents; Community Programs; Counseling Services; Drug Abuse; Educational Needs; Health; Health Behavior; Interpersonal Competence; Mass Media Effects; Personality Traits; Prevention; Secondary Education; Social Influences; Values Education; Collected Works, General; Information Analyses